2018
DOI: 10.3390/ijerph15030519
|View full text |Cite
|
Sign up to set email alerts
|

WHO Environmental Noise Guidelines for the European Region: A Systematic Review on Environmental Noise and Effects on Sleep

Abstract: To evaluate the quality of available evidence on the effects of environmental noise exposure on sleep a systematic review was conducted. The databases PSYCINFO, PubMed, Science Direct, Scopus, Web of Science and the TNO Repository were searched for non-laboratory studies on the effects of environmental noise on sleep with measured or predicted noise levels and published in or after the year 2000. The quality of the evidence was assessed using GRADE criteria. Seventy four studies predominately conducted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
315
1
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(349 citation statements)
references
References 107 publications
12
315
1
21
Order By: Relevance
“…The review by Allen et al also showed limited support for adjusting the bedroom light to as dark (i.e., only two studies) and as quiet (i.e., only two studies) as possible for better sleep [17]. In contrast, a recent review of the WHO found evidence for a relationship between ambient noise and inadequate sleep [40]. Furthermore, a previous study (2017) where 11-12 year old multi-ethnic adolescents identified sleep-disturbing household activities, found that disorganization in the home environment such as TV or noise disturbance, family members phone calling, or night-time home visitors, were related to disturbed sleep [41].…”
Section: Discussionmentioning
confidence: 99%
“…The review by Allen et al also showed limited support for adjusting the bedroom light to as dark (i.e., only two studies) and as quiet (i.e., only two studies) as possible for better sleep [17]. In contrast, a recent review of the WHO found evidence for a relationship between ambient noise and inadequate sleep [40]. Furthermore, a previous study (2017) where 11-12 year old multi-ethnic adolescents identified sleep-disturbing household activities, found that disorganization in the home environment such as TV or noise disturbance, family members phone calling, or night-time home visitors, were related to disturbed sleep [41].…”
Section: Discussionmentioning
confidence: 99%
“…Da die Kategorien 2-5 relativ gering besetzt waren, wurden die Kategorien 2 und 3 zu "etwas/mittel gestört" und die Kategorien 4 und 5 zu "stark/sehr stark gestört" entsprechend einer früheren Studie zusammengefasst [16]. Obwohl in der Frage das Wort "gestört" verwendet wurde, interpretieren wir die Antwort im Sinne einer Lärmbelästigung, da nicht nach konkreten Ereignissen wie Aufwachen oder Einschlafen gefragt wurde, wie es bei der Beurteilung von Störungen üblicherweise der Fall ist [31]. Zudem werden die Begriffe "gestört" und "belästigt" im Deutschen synonym verwendet [32].…”
Section: Erfassung Der Lärmbelästigungunclassified
“…Possible effects of radiofrequency (RF) electromagnetic fields (EMF) on sleep have been investigated in numerous studies in the past. Such studies are of particular interest because human sleep is commonly seen as a sensitive indicator for the impact of various environmental factors on central nervous processes [Basner and McGuire, 2018; Harding et al, 2019]. However, so far RF EMF‐related sleep studies have mainly focused on signals emitted by cellular mobile communication systems, such as the global system for mobile communication in frequency ranges around 900 and 1,800 MHz [Borbely et al, 1999; Huber et al, 2000; Loughran et al, 2005, 2012; Hinrichs et al, 2005; Hung et al, 2007; Regel et al, 2007; Arnetz et al, 2007; Danker‐Hopfe et al, 2010, 2011, 2016, 2019; Lowden et al, 2011; Schmid et al, 2012a,b; Lustenberger et al, 2013, 2015], the universal mobile telecommunications system in the frequency range between 1,900 and 2,000 MHz [Danker‐Hopfe et al, 2011, 2016; Nakatani‐Enomoto et al, 2013; Lowden et al, 2019], and the terrestrial trunked radio in the frequency range around 385 MHz [Danker‐Hopfe et al, 2019].…”
Section: Introductionmentioning
confidence: 99%